Determination of Advertising Tax in the Event of Determining Tax Payable is Based on the Display of Advertising in Accordance With Regional Regulation of Surabaya City Number 7 of 2023 Concerning Regional Tax - Yohanes Franklin; Rusdianto Sesung (Journal of Law, Politic and Humanities, 2025)
Taxes are a source of state income which is very important for the continuity of government programs and activities. One type of tax that is the object of regional tax is Advertisement Tax, which is imposed on the basis of carrying out advertisements in an area. Advertisement Tax Debt arises as the advertisement is carried out, although tax payments can only be made after the Regional Tax Assessment Letter is issued based on a request from the advertisement operator. If the advertisement organizer does not register the advertisement, the Regional Government can issue a Regional Tax Assessment Letter ex officio to encourage optimization of advertisement tax revenues. Apart from that, advertising must also pay attention to the city planning and existing space to maintain the aesthetics of the city. Regional Regulation Number 5 of 2019 is expected to provide legal certainty and ensure that the implementation of advertising does not conflict with spatial planning. Even though the Advertisement Tax has been paid, the issuance of a permit to operate advertisements cannot be done simply without paying attention to the provisions in regional regulations. As part of efforts to control advertisements and to ensure tax optimization in line with spatial planning provisions, taxes must carry out a regular function through the application of tax disincentives to advertisements that do not comply with existing planning regulations